The Copper concentration variation to physical properties of high copper amalgam alloy - Aminatun Aminatun (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2006)
The function of copper (Cu) inside amalgam is to increase hardness and impact force and to decrease thermal expansion coefficient. In general, amalgam which is used in dentistry and available in the market is contain Cu 22%, while the maximum Cu concentration is 30%. It is necessary to determine the concentration Cu does generate the best physical properties to be used as dental restorative agent. Amalgam is made by mixing blended-metal Ag-Sn-Cu (with Cu concentration of 13%, 21%, 22%, and 29%) and Hg, stirred manually in a bowl for 15 minutes,leave it in temperature 27°C for 24 hours to become hardened. The result of X-Ray Diffractometer (XRD), analyzed by Rietveld method and Rietica program, shows amalgam with Cu 29% concentration for Cu3Sn compound density is 31.790 sma/Å3, for Ag2Hg3 compound is 41.733 sma/ Å3, a Cu3Sn relative weight percentage of 43.23%, Ag2Hg3 of 54.54%, Cu 7Hg6 of 2.23% and hardness of Cu 29% is 90.700 ± 0.005 kgf/mm2. These numbers are the highest values on Cu 29% concentrations compared to other copper concentration variants. Whereas amalgam thermal expansion coefficient on Cu 29% is (2.17 ± 0.91)10-3 mm/°C is the lowest value compared to other Cu concentration. The conclution is that adding Cu concentration into amalgam will increase density value, Cu3Sn relative weight percentage, hardness level and will decrease amalgam thermal expansion coefficient. Amalgam 29% Cu concentration has better physical properties compared to amalgam Cu 22% concentration.